Pengaruh Penambahan Infra Merah pada Contract Relax Stretching terhadap Fleksibilitas Pemain Futsal SMP 1 Klaten - Rima Yunitasari (CV. Syntax Corporation Indonesia, 2021)
This study aims to determine the effect of infra red with the contract relax stretching on the player futsal SMP 1 Klaten. Methods this research uses experimental research with quantitative approach and the desain One Group Pretest-Posttest Design. the number of sample of this study amounted to 20 samples, the results of research using the test and Paired sample t-test group 1 Contract Relax Stretching (p-value) 0.0139 Ha is accepted and Ho is rejected and it was concluded there is the influence of Contract Relax Stretching on flexibility, in group 2 infra red and Contract Relax Stretching (p-value) 0.0000 that Ha is accepted and Ho is rejected, it can be concluded there is a significant influence on the infra red and Contract Relax Stretching. Conclusion this study is the addition of infra red on the provision of Contract Relax Stretching can increase flexibility on the player futsal SMP 1 N Klaten to the fullest.